Da maturação à felicidade: o teatro em sala de aula - ensinando a ser feliz - EDUARDO RELLYSON MENEZES ARAUJO (2023)
From maturation to happiness: theater in classroom - teaching to be happy This research had as object of study, to provide an ability to develop a free, democratic, resilient and self-confident thought that stimulates the power for happiness, through theater classes in the classroom. To this end, we explore the philosophical understanding of happiness throughout human existence, built by Western civilization, analyzing concepts that historically identify and contextualize human beings in their time and society, and their search for happiness. We observe, through the analysis made by Marilena Chauí (2008) on ideology; and from education through love, by Humberto Maturana (1995), the precepts that show us paths to happiness. Methodologically, we will appropriate the pedagogy of Paulo Freire (1987, 1996, 2001) as a way of valuing and respecting the teacher's place of speech, while oppressed by a society that dictates the ideology and makes the moral rules of the society in which they are inserted. Thus, we will use the Theatrical Games and Theater of Improvisation, by Viola Spolin (1906 - 1994), contributing to the development of themes that can achieve the desired awakening in those who are inserted causing the expected becoming, such themes are proposed directly or implied in the contexts addressed in art classes, supported by the concepts also provided by Augusto Boal (1977,2005,2008), to compose the students' freedom of thought, contextualizing them in their environment, their community, their perceived reality.